(3QSGdI aj GdYUjQs - (3GdHgHgGfj, eMeO GdHgHgGfj, eMeO HGbQ Hf eMeO Cced GdCUagGfj, J (B1205(3g` (B1891(3es ((3cQHdGAs)
(3ChdgG (B:s
(3ChdgG(B: (3eSFdI aj Mce YUjQ GdJeQ hGdRHjH, bGd ehdGfG ebOS GdCQOHjdj(B: (3ajgeG NdGa hGdeTghQ GdMd hbjd HGdJMQje hjXgQ CjkVG Gdbhd HGdfLGSIs
(3BNQgG (B:s
(3BNQgG(B: (3hCeG GdNGUI aHYO JSdje PGc hEfeG gh ef aJGhi abgGFfG GdeJCNQhf Ydi Cf GdcdGe aj eYQaI GdRHjHI Ch ZjQ eYdhe ef GdeGFY dG jOd Ydi chfg efgG SjeG GdNGdU Hd dYdg dG JCed aj YOe chfgG eGA GdRHjH GdNGdU Hd dYdgG djSJ ef GdeGFYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf L (B3: 154s
(3GdPQjYI, L (B15: 200s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis